THE EFFECT OF TAXES AND LEVIES ON LOCAL ORIGINAL REVENUES IN CITY GOVERNMENTS IN ACEH PROVINCE IS VIEWED FROM AN ISLAMIC PERSPECTIVE - Zulkarnain, Muhammad (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2022)
THE EFFECT OF TAXES AND LEVIES ON LOCAL ORIGINAL REVENUES IN CITY GOVERNMENTS IN ACEH PROVINCE IS VIEWED FROM AN ISLAMIC PERSPECTIVE Abstract Purpose: This study aims to investigate the impact of taxes and fees on the local revenue of five city governments in Aceh Province, examining it from an Islamic perspective Design/methodology/approach: The research adopts a quantitative descriptive approach, utilizing panel data with a cross-section of five city governments (Banda Aceh, Sabang, Langsa, Lhokseumawe, and Subulusalam) and a time series spanning from 2008 to 2021. The data analysis employs panel data regression. Findings: The results reveal a significant influence of taxes and fees on regional revenue in the five city governments of Aceh Province. The coefficient of determination (R2) indicates that 81% of regional revenue can be explained by the variables of taxes and fees. However, it is important to note that the study has limitations, focusing solely on city governments and excluding the broader government of Aceh. Research limitations/implications: The limitations of this research include its exclusive focus on city governments and the omission of the entire Aceh government. Future studies could explore the broader regional context. Practical implications: The research provides valuable insights for city governments in enhancing the welfare of their constituents through local revenue generated from regional taxes and levies. Keywords: Tax, Retributions, Local Revenue, Islamic Perspective, Aceh Province. PENGARUH PAJAK DAN RETRIBUSI TERHADAP PENDAPATAN ASLI DAERAH DI PEMERINTAH KOTA DI PROVINSI ACEH DILIHAT DARI PERSPEKTIF ISLAM Abstrak Tujuan: Penelitian ini bertujuan untuk menyelidiki dampak pajak dan biaya terhadap pendapatan asli daerah dari lima pemerintah kota di Provinsi Aceh, memeriksanya dari perspektif Islam Desain/metodologi/pendekatan: Penelitian ini mengadopsi pendekatan deskriptif kuantitatif, memanfaatkan data panel dengan penampang lima pemerintah kota (Banda Aceh, Sabang, Langsa, Lhokseumawe, dan Subulusalam) dan rangkaian waktu yang mencakup dari 2008 hingga 2021. Analisis data menggunakan regresi data panel. Kesimpulan: Hasilnya menunjukkan pengaruh yang signifikan dari pajak dan biaya terhadap pendapatan daerah di lima pemerintah kota di Provinsi Aceh. Koefisien determinasi (R2) menunjukkan bahwa 81% dari pendapatan daerah dapat dijelaskan oleh variabel pajak dan biaya. Namun, penting untuk dicatat bahwa penelitian ini memiliki keterbatasan, hanya berfokus pada pemerintah kota dan mengecualikan pemerintah Aceh yang lebih luas. Keterbatasan / implikasi penelitian: Keterbatasan penelitian ini termasuk fokus eksklusifnya pada pemerintah kota dan kelalaian seluruh pemerintah Aceh. Studi masa depan dapat mengeksplorasi konteks regional yang lebih luas. Implikasi praktis: Penelitian ini memberikan wawasan berharga bagi pemerintah kota dalam meningkatkan kesejahteraan konstituen mereka melalui pendapatan daerah yang dihasilkan dari pajak dan retribusi daerah. Kata kunci: Pajak, Retributions, Pendapatan Daerah, Perspektif Islam, Provinsi Aceh.